Multi-criteria evaluation of land cover policies using fuzzy AHP: The case of Turkey - Demirel, Tufan; Musdal, Hande (ATLANTIS PRESS, 2007)
In our world, the land cover and use strategies gain importance since scarce resources decrease. The world is not able adequately to feed the population and the food deficit is growing parallel to the growth of population. This paper proposes a multi-criteria decision-making method using fuzzy Analytic Hierarchy Process for the evaluation of alternative land cover policies under various confidence levels of the Decision Maker with respect to his/her attitudes toward risk.
Keywords: fuzzy AHP; hierarchy; land cover policies; agriculture; REGION; Computer Science; Mathematics